Influencing Factors of Student Satisfaction With the Teaching Quality of Fundamentals of Entrepreneurship Course Under the Background of Innovation and Entrepreneurship - Gao, Shuai; Zhuang, Jiaojiao; Chang, Yuteng (Frontiers in Education, 2021)
Innovation and entrepreneurship education is a key way to cultivate applied talents in colleges and universities. This article aimed to optimize the teaching quality of the Fundamentals of Entrepreneurship courses by constructing a conceptual model of "teaching quality–student satisfaction."Teaching quality is divided into four indicator elements, teaching content, teaching methods, teaching conditions, and teaching management. A student satisfaction questionnaire was designed to measure the teaching quality of a Fundamentals of Entrepreneurship course. Survey data from Linyi University were analyzed using SPSS.20 software to investigate the current status of the teaching quality of the Fundamentals of Entrepreneurship course and to determine the main factors affecting student satisfaction with the teaching quality. On this basis, suggestions are put forward to improve student satisfaction with the teaching quality of Fundamentals of Entrepreneurship courses, and to provide empirical evidence and recommendations for continuously improving the teaching quality of Fundamentals of Entrepreneurship courses, thereby improving college students' employment and entrepreneurship ability.